2015
DOI: 10.1002/14651858.cd010023.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography versus magnetic resonance imaging versus bone scintigraphy for clinically suspected scaphoid fractures in patients with negative plain radiographs

Abstract: Computed tomography versus magnetic resonance imaging versus bone scintigraphy for clinically suspected scaphoid fractures in patients with negative plain radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 91 publications
0
59
0
4
Order By: Relevance
“…Key factors in a meta-analysis are the number and the methodological quality of the included studies and the degree of heterogeneity in their estimates of diagnostic accuracy [42]. Heterogeneity in diagnostic test accuracy reviews is expected and the possibilities of performing meta-regression analyses will depend on the number of studies available for a specific index test that provide sufficient information [39]. The data from the included studies were combined when studies showed no limitations according to QUADAS-2 and had no other forms of bias (e.g.…”
Section: Heterogeneitymentioning
confidence: 99%
See 3 more Smart Citations
“…Key factors in a meta-analysis are the number and the methodological quality of the included studies and the degree of heterogeneity in their estimates of diagnostic accuracy [42]. Heterogeneity in diagnostic test accuracy reviews is expected and the possibilities of performing meta-regression analyses will depend on the number of studies available for a specific index test that provide sufficient information [39]. The data from the included studies were combined when studies showed no limitations according to QUADAS-2 and had no other forms of bias (e.g.…”
Section: Heterogeneitymentioning
confidence: 99%
“…However, MRI is more specific and better for confirming scaphoid fractures when compared to BS. According to the Cochrane review of Mallee et al, statistically BS is the best diagnostic modality for establishing a definitive diagnosis in clinically suspected fractures when radiographs appear normal, but the number of overtreated patients is substantially lower with CT and MRI [39]. Moreover, physicians must keep in mind that BS is more invasive than the other modalities.…”
Section: Diagnostic Accuracy Of Imaging Of Carpal Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of other imaging modalities has been widely researched and has confirmed high sensitivity and specificity values for both magnetic resonance imaging (MRI) and computed tomography (CT). [13][14][15][16][17] In 2016 NICE published guidance on the imaging of suspected scaphoid fractures 4 , which concluded that organisations should consider MRI as the first-line imaging investigation. It has the advantage of not using ionising radiation, and also provides excellent visualisation of other bony or soft tissue injuries.…”
Section: Introductionmentioning
confidence: 99%